The Relationship between Sleep Quality and Happiness in Men with Coronary Artery Disease - Davoud Ezzati; Naimeh Mashinchi Abbasi; Hossein Namdar; Naser Khezerlou Aghdam; Touraj Hashemi Nosrat-abad; Ali Shiri; Babak Sadeghi; Marzie Salehi (Publisher: Shahid Beheshti University of Medical Sciences, 2019)
Background and Aim: Good sleep quality has beneficial effects on happiness and being unhappy is significantly associated with negative cardiac outcomes. The present research aimed at studying the relationships between sleep quality and happiness in male coronary patients. Methods: One hundred male coronary patients that having been referred to Madani Heart Hospital, Tabriz, Iran, completed the Pittsburgh Sleep Quality Index (PSQI) and Oxford Happiness Questionnaire (OHQ). All participants were selected by purposive sampling (aged 37 to 67 years). Data were analyzed by multiple regression (simultaneous method) through the SPSS 18 software.Results: There was a significant negative difference between happiness with sleep disturbances and use of sleeping medication in coronary patients. Conclusion: This study showed that poor sleep quality in coronary patients has negative effects on their happiness. Therefore, the quality of sleep in these patients should be given more consideration by community health care providers.Keywords: Sleep Quality, Happiness, Coronary Artery Disease.